CELLULOSE FROM VARIOUS PARTS OF SORANOVSKII MISCANTHUS - Yu. A. Gismatulina; V. V. Budaeva; S. G. Veprev; G. V. Sakovich; V. K. Shumny (Вавиловский журнал генетики и селекции)
The chemical composition of the Soranovskii Miscanthus variety harvested in 2011 and 2012 was separately determined in the whole plant, leaves, and stem. In all cases, cellulose was found to prevail in the Miscanthus stem, and non-cellulosic components (the fat-wax fraction, ash, and lignin), in leaves. Cellulose samples were for the first time obtained from leaves and stems separately by two methods (nitric-acid and combined). The best quality cellulose was derived from stems. For instance, cellulose isolated from stems by the nitric-acid process was better than that from leaves, which was expressed as a higher α cellulose content (94,4 % versus 91,7 %) and polymerization degree (800 versus 580), as well as low weight fractions of non-cellulosic components: ash (0,07 % versus 1,01 %) and acid-insoluble lignin (0,45 % versus 1,51 %). The same tendency is observed in celluloses produced by the combined method: Cellulose from stems had better quality than that from leaves; specifically, it had a greater polymerization degree (1040 versus 640) and lower weight fractions of non-cellulosic components: ash (0,14 % versus 0,75 %), acid-insoluble lignin (0,88 % versus 4,2 %), and pentosans (6,8 % versus 8,53 %). It is obvious that cellulose obtained by the nitric-acid method can be suitable for chemical modifications, including nitration. Cellulose from the combined process can be utilized in paper industry.